Penerapan Peraturan Daerah Kota Denpasar Nomor 3 Tahun 2015 Tentang Pengelolaan Sampah - Dewa Gede Agus Anjaswara; I Gusti Bagus Suryawan; Luh Putu Suryani (Warmadewa Press, 2020)
The city of Denpasar has not been able to carry out waste management properly, even though waste management is very important to reduce the volume of waste, and it can even use waste into useful objects or products. Denpasar City tries to manage waste in Denpasar. The purpose of this research is to find out how the implementation of Denpasar City Regulation Number 3 of 2015 concerning Waste Management and to find out the supporting and inhibiting factors of the enactment of Denpasar City Government Regulation Number 3 of 2015 concerning Waste Management. This study was designed using empirical legal research with a statutory approach. The data collection techniques used in the study were interviews and documentation. The results show that the action of the Denpasar city government against violations of the Regional Regulation of the City of Denpasar Number 3 of 2015 concerning waste management is to implement minor crimes against offenders where those who violate are tried in light criminal court (Tipiring). Then, the supporting and inhibiting factors for the enforcement of Regional Regulation Number 3 of 2015 on Waste Management are the legal basis for cleanliness management that has been issued by the Denpasar City Government in the form of Legislation, Regional Regulations, and the Mayor of Denpasar. Inhibiting factors for the enforcement of Sanctions by Regional Regulation No.3 of 2015 on Waste Management, namely factors of law enforcement officers, facilities and infrastructure factors, and community factors.